1999
DOI: 10.1002/(sici)1099-0879(199907)6:3<202::aid-cpp203>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative preparation for surgery: an analysis of the effects of relaxation and information provision

Abstract: The two objectives of this study were: (1) to replicate previous findings on the effects of relaxation in the preparation for surgery, and (2) to analyse the interaction effect between type of intervention (i.e., relaxation and information provision) and coping style (i.e., high versus low monitoring) on patients' pain level and the return to normal daily activities.Ninety cholecistectomy patients, who accepted participation in the study, were randomly assigned to one of three groups. Patients in the first gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…9,10 In addition, stress has been linked to the slower healing of wounds through psychoneuroimmunological mechanisms 11 and reducing anxiety has been defined as one of the principles of conducting a pre-anaesthetic consultation. 12 Although preoperative information is available, consideration should be given to including those categories of information which improve recovery.…”
Section: Information-givingmentioning
confidence: 99%
“…9,10 In addition, stress has been linked to the slower healing of wounds through psychoneuroimmunological mechanisms 11 and reducing anxiety has been defined as one of the principles of conducting a pre-anaesthetic consultation. 12 Although preoperative information is available, consideration should be given to including those categories of information which improve recovery.…”
Section: Information-givingmentioning
confidence: 99%
“…Although some studies have shown associations between preoperative psychological characteristics and recovery, results are ambiguous. 8,[31][32][33][34][35][36][37] In our study it seemed that mode of anaesthesia played an important role in enabling stress coping capacity to aid recovery.…”
Section: Discussionmentioning
confidence: 97%
“…By giving the patient thorough and detailed information about the operation and the postoperative period, the fast‐track programme prepares the individual for a faster recovery 7 . Providing accurate information prior to gynaecological surgery and using regional anaesthesia reduces postoperative analgesic requirements, and results in a more rapid return to full health 7,8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether patients will benefit from additional information depends on their coping styles described as information-avoiding or information-seeking. Others suggested that providing patients with sensory information before surgical procedures is not advantageous to the changes in anxiety and pain levels (7).…”
Section: L'effet Du Niveau D'information Et Des Modes D'adaptation Sumentioning
confidence: 99%